Concrete thermal stress analysis during tunnel construction. (June 2019) - Wang, Xianfeng; Chen, Qi; Tao, Jun; Han, Rui; Ding, Xiaobo; Xing, Feng; Han, Ningxu
In order to propose an optimised construction plan and prevent and control the possible occurrence of cracks in concrete structures during construction, a detailed simulation of construction stages is required. The temperature and thermal stresses during the construction of a double-hole, double-deck concrete tunnel structure were analysed in this study, in which the analysis of the early-aged behaviour of a structure was performed considering actual construction conditions, and the cracking conditions were predicted. It was found that the temperature trends obtained from the simulated results were in good agreement with actual data, which indicates the reliability of the simulation results. In addition, the distribution of thermal stresses in the structure indicated that the tunnel structure was at risk of cracking at a number of stress concentration areas under the construction conditions. A parameter analysis of different factors, including the initial concrete temperature (25°C, 30°C, and 35°C), formwork stripping time (48 h, 72 h, and 96 h), and the construction season ambient temperature (summer and winter), was conducted. The formwork stripping time did not have a significant influence. It is recommended that the initial concrete temperature should be controlled to below 30°C during construction.